(untitled) (Research, Society and Development, 2020)
Beer has gain great visibility and esteem in Brazil, becoming a higher quality product over time. In face of this visibility, beer has been reaching more varieties and regional fruits are being used more and more. The mesquite tree is a plant of great popularity in the Northeast region of Brazil, with a high potential to make new products, but little explored, becoming a plague due to its easy germination. Their pods are highly fermentative, making them a potential beer ingredient. The objective of this paper is to make a craft beer using the mesquite fruit as a fermentable adjunct, and compare it with a wheat beer, analyzing them microbiologically, chemically and sensorially. The method used to craft this beer was Brew in a Bag. A drinkable beer was obtained with higher alcohol by volume than the average to the style studied. Physicochemical and microbiological tests were acceptable to the category of the product. Besides that, the new beer got a great public acceptance. Therefore, a good beer with high selling capacity was obtained.